PENGARUH PANDEMI COVID-19 TERHADAP KINERJA KEUANGAN PERBANKAN PADA BANK UMUM KONVENSIONAL DI ASEAN-5 TAHUN 2020-2022 - Luthfiati, Fitria; Pangestuti, Irene Rini Demi (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to examine the effect of the COVID-19 pandemic on banking financial performance. The variable used in this study is the COVID-19 pandemic as the independent variable, price to book value (PBV) as the dependent variable. In addition, Leverage and Cash to Total Assets are used as control variables.This study uses secondary data with a population of 93 conventional commercial banks in ASEAN-5 countries, that is Indonesia, Singapore, Malaysia, Thailand and Philippines. This study using the purposive sampling method, 80 conventional commercial banks in ASEAN-5 countries were found as research samples. The analytical method used in this research is multiple linear regression analysis.The results of this study indicate that the COVID-19 pandemic has a significant positive effect on financial performance as measured by Price to Book Value (PBV). Leverage has a significant positive effect on financial performance as measured by price to book value (PBV), but Cash to Total Assets has a negative effect on price to book value (PBV)